Effects of foot strike pattern and foot arch on leg stiffness in running - Tan, Jebsen (2019)
Running is a very common type of physical activity. Runners typically run using a fore foot or heel strike pattern, either subconsciously or consciously. Individual’s foot arch also plays a vital role in running as the foot is known to absorb impact from the contact between the foot and the ground during the run. However, little is known about the relationship between the foot arch and the foot strike pattern and whether it has any impact on the lower limb kinematic variables. The main aim of this research was to find out if different foot arch affects leg stiffness and other lower limb variables when using forefoot or heel strike pattern in running. 23 male and female participants were recruited and screened for their foot arch (6 high arch and 17 low arch) using a plantar pedography platform to determine their arch height index (AHI), the navicular drop test and calcaneal stance position test. Participants then went through 2 running trials on an instrumented treadmill using forefoot strike and heel strike running pattern. Their leg stiffness, vertical stiffness, loading rate and max peak force were then calculated. No signification interaction was found between foot strike pattern and foot arch level for leg stiffness(p ≤ 0.74) and vertical stiffness(p ≤ 0.33) while a significant but minimal effect was found for max peak force(p ≤ 0.04, Ƞ² = 0.19) and loading rate(p ≤ 0.04, Ƞ² = 0.19). Therefore, individual should not need to be overly concerned about performance or injury rate in running regardless of their foot arch